Faktor-Faktor yang Berhubungan dengan Perilaku Pencarian Pelayanan Kesehatan (Health Seeking Behavior) pada Santri di Pondok Pesantren Al Bisyri Tinjomoyo Semarang - Adi Nur Rahman; Priyadi Nugraha Prabamurti; Emmy Riyanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Islamic boarding school has a classic problem that students health problems and problems of the disease. A disease that is often suffered by the students at the boarding school, among others, scabies and diarrhea. Poor quality of life of students in boarding school due to students having a simple behavior and lack of facilities in the boarding school, especially health care facilities. This is why the students are less concerned about finding treatment when they feel sick. The purpose of this study was to analyze factors associated with health seeking behavior on students at islamic boarding schools Al Bisyri Tinjomoyo Semarang. This research used analytic survey with cross sectional study. The population of all students of both men and women living in the islamic boarding school Al Bisyri are 73 students and the number of samples taken as many as 73 students using total population method. This study using univariate, bivariate with chi square test and multivariate analysis. The results showed that students who behave good health seeking behavior by 58.9%. Students are early teens (47,9%), female (58,9%), junior high school (80,8%), came from outside the city of Semarang (86,3%) and have lived in the islamic boarding school for 1-3 years (71,2%). Chi-square test results showed that the variables associated with health seeking behavior: access to health care (p-value = 0.032), the perception of pain (p-value = 0.013) and the need for health care (p-value = 0.007). Multivariate analysis showed that students who need health care the larger 4 to 5 times to commit health seeking behavior better than students who do not need health care. From this research, it needs the support of kiai, ustadz and administrator boarding against health seeking behavior students in the form of directives given to the students as a lecture or when students learn in order to change the mindset of students against health seeking behavior.